Teacher Representations in Immersive Environments Through Holograms: A Narrative Review on the Perspectives and Challenges - Santos, Sanval Ebert de Freitas; Cruz, Leonardo Cardia da; Durval, Anna L. A.; Mendes, Pedro Tanajura; Silva, José; Ferreira, Yasmim Thasla Santos; Winkler, Ingrid (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
This paper discusses the perspectives and challenges related to the use of holograms in education, focusing on three-dimensional teacher representation and the creation of immersive environments. The investigation was conducted through a narrative literature review, based on scientific and technical publications released between 2013 and 2025 in Scopus, Web of Science, IEEE Xplore, ERIC, Google Scholar, and the CAPES Digital Library. The results indicate that the adoption of holographic technologies in educational contexts faces structural, pedagogical, operational, and institutional limitations. Among the main obstacles identified are the need for specific infrastructure, the lack of ongoing technical training, difficulties in integrating with learning platforms, and challenges related to accessibility and ethics. On the other hand, the analyzed experiences suggest possibilities for enhancing teacher presence, visual mediation, and the personalization of educational interactions through three-dimensional representations. The analysis contributes to mapping the conditions that influence the implementation of these resources and proposes pathways for pedagogical experimentation with advanced visual technologies across different educational levels.